Instillation of Povidone-Iodine as A Management of Chyluria: A Case Report - Pande Made Wisnu Tirtayasa; Gede Wirya Kusuma Duarsa (European Journal of Case Reports in Internal Medicine, 2022)
Background: Chyluria is usually associated with parasitic disease caused by Wuchereria bancrofti and is rare in non-endemic regions. The management of chyluria varies according to the severity of the condition. This report describes a case of mild chyluria and successful treatment using sclerotherapy.